Imagining otherness: on translation, harm and border logic. (3rd July 2019) - Maitland, Sarah
ABSTRACT: Using theoretical frameworks drawn from the fields of cultural anthropology and political philosophy, this article pursues connections between disparate discussions of representation and identity politics to consider the determining role that translation plays in constructing relations of power between the translating 'self' and the translated 'other'. With reference to a theatre translation case study, it argues that the act of translation subordinates the position of the other to the biographical journey of the translator. By transforming the status of a living author from one of writing subject to representational object, translation is conceptualised as a form of so-called 'status misrecognition' that threatens to displace the author's agency in translation, preventing them from participating as a peer in the passage from imagination to realisation in the target language. By emphasising greater author engagement in the translation process, this article calls for the first steps in a translational 'politics of recognition' by which the shape of translations would be informed by an increased valorisation of the status of authors as active participants in, rather than objects of, the imaginative acts that lead to translations.